Genetic Polymorphisms of Interleukin-1 Alpha and the Vitamin D Receptor in Mexican Mestizo Patients with Intervertebral Disc Degeneration - Salvador Cervin Serrano; Dalia González Villareal; Maribel Aguilar-Medina; Jose Guillermo Romero-Navarro; Jose Geovanni Romero Quintana; Eliakym Arámbula Meraz; Ignacio Osuna Ramírez; Veronica Picos-Cárdenas; Julio Granados; Iris Estrada-García; Guzman Sánchez-Schmitz; Rosalío Ramos-Payán (International Journal of Genomics)
Intervertebral disc degeneration (IDD) is the most common diagnosis in patients with back pain, a leading cause of musculoskeletal disability worldwide. Several conditions, such as occupational activities, gender, age, and obesity, have been associated with IDD. However, the development of this disease has strong genetic determinants. In this study, we explore the possible association between rs1800587 (c.-949C>T) of interleukin-1 alpha (IL1A) and rs2228570 (c.2T>V) and rs731236 (c.1056T>C) of vitamin D receptor (VDR) gene polymorphisms and the development of IDD in northwestern Mexican Mestizo population. Gene polymorphisms were analyzed by polymerase chain reaction followed by restriction fragment length polymorphism, in two groups matched by age and gender: patients with symptomatic lumbar IDD n=100 and subjects with normal lumbar-spine MRI-scans n=100. Distribution of the mutated alleles in patients and controls was 27.0% versus 28.0% P=0.455 for T of rs1800587 (IL1A); 53.0% versus 58.0% P=0.183 for V of rs2228570 (VDR); and 18.0% versus 21.0% P=0.262 for C of rs731236 (VDR). Our results showed no association between the studied polymorphisms and IDD in this population. This is the first report on the contribution of gene polymorphisms on IDD in a Mexican population.